ECPR—extracorporeal cardiopulmonary resuscitation - Kumar, Kuppuswamy Madhan (Indian J Thorac Cardiovasc Surg, 2021)
Extracorporeal cardiopulmonary resuscitation (ECPR) is a salvage procedure in which extracorporeal membrane oxygenation (ECMO) is initiated emergently on patients who have had cardiac arrest (CA) and on whom the conventional cardiopulmonary resuscitation (CCPR) has failed. Awareness and usage of ECPR are increasing all over the world. Significant advancements have taken place in the ECPR initiation techniques, in its device and in its post-procedure care. ECPR is a team work requiring multidisciplinary experts, highly skilled health care workers and adequate infrastructure with appropriate devices. Perfect coordination and communication among team members play a vital role in the outcome of the ECPR patients. Ethical, legal and financial issues need to be considered before initiation of ECPR and while withdrawing the support when the ECPR is futile. Numerous studies about ECPR are being published more frequently in the last few years. Hence, keeping updated about the ECPR is very important for proper selection of cases and its management. This article reviews various aspects of ECPR and relevant literature to date.